Proposal of a method system for interpersonal communication in the Higher Education context - Marivel C. Jurado Ronquillo (Medisur, 2017)
Curriculum transformation in the university majors in Ecuador has generated a growing concern for studying different aspects of interpersonal communication in the teaching-learning process. This paper is aimed at  presenting a system of methods for interpersonal communication in the teaching-learning process. The proposed system supports the possibilities offered by the problem methods at different phases of the teaching-learning process, which is achieved by promoting dialogue, cognitive and affective exchange among all those who participate, share and contribute to the learning of others. The system of methods for interpersonal communication in the teaching-learning process suggests a change in the teacher's role and in the way in which this process is conceived and developed. Due to its didactic nature, it is a system which explains interpersonal communication as the center of the teaching-learning process.